2005
DOI: 10.1099/vir.0.80844-0
|View full text |Cite
|
Sign up to set email alerts
|

A single immunization with a rhabdovirus-based vector expressing severe acute respiratory syndrome coronavirus (SARS-CoV) S protein results in the production of high levels of SARS-CoV-neutralizing antibodies

Abstract: Foreign viral proteins expressed by rabies virus (RV) have been shown to induce potent humoral and cellular immune responses in immunized animals. In addition, highly attenuated and, therefore, very safe RV-based vectors have been constructed. Here, an RV-based vaccine vehicle was utilized as a novel vaccine against severe acute respiratory syndrome coronavirus (SARS-CoV). For this approach, the SARS-CoV nucleocapsid protein (N) or envelope spike protein (S) genes were cloned between the RV glycoprotein G and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 30 publications
(38 reference statements)
2
65
0
Order By: Relevance
“…A number of studies have shown that S protein and its fragments induce SARS-CoV-neutralizing antibodies [16,[24][25][26][27][28][29][30][31][32][33]. The receptor-binding domain (RBD) in the S1 region plays a critical role in the neutralizing antibody induction as well as ACE2 binding and viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have shown that S protein and its fragments induce SARS-CoV-neutralizing antibodies [16,[24][25][26][27][28][29][30][31][32][33]. The receptor-binding domain (RBD) in the S1 region plays a critical role in the neutralizing antibody induction as well as ACE2 binding and viral entry.…”
Section: Discussionmentioning
confidence: 99%
“…These vaccine candidates are able to induce protective immune responses against SARS-CoV, including NA and T cell immune responses (14, 19 -21). A majority of these vaccines are based on the SARS-CoV S protein (22)(23)(24)(25).…”
Section: Intranasal Vaccination Of Recombinant Adeno-associated Virusmentioning
confidence: 99%
“…Its S protein is responsible for virus binding to the receptor, angiotensin-converting enzyme 2 (ACE2), and subsequent virus entry into the host cells [10,11]. The S protein of SARS-CoV has also been demonstrated to be the main antigen in inducing high titer of neutralizing antibodies [12][13][14], and in eliciting protective immunity against infection in challenged animals [15][16][17]. Thus, it is implied to be the main target in development of SARS vaccines.…”
Section: Introductionmentioning
confidence: 99%